STAKEHOLDER COLLABORATION IN EMPOWERING LOCAL POTENTIAL-BASED TOURISM AWARENESS GROUPS IN PANGARENGAN, SAMPANG - Buadah; Sri Kamariyah; Zainal Fatah (International Journal of Multidisciplinary Reseach, 2026)
This research examines the dynamics of stakeholder collaboration in empowering the Tourism Awareness Group (Pokdarwis) based on local potential in Pangarengan, Sampang Regency. The study is motivated by the shift in public administration toward collaborative governance to optimize coastal resources such as salt ponds and mangrove ecosystems. Using a descriptive qualitative approach, data were gathered through interviews with representatives from the tourism department, village governments, Pokdarwis members, academics, and the private sector. The results indicate that collaboration remains in a transitional phase characterized by "pseudo-collaboration," where top-down patterns from the district government and institutional egos regarding coastal land-use permits hinder Pokdarwis autonomy. Findings reveal that empowerment efforts often prioritize ceremonial physical assistance, such as providing uniforms, while neglecting substantive needs like technical training in digital marketing and product branding. However, a significant indicator of effectiveness is observed in the strengthening of social capital through independent youth initiatives in mangrove conservation. The study concludes that the sustainability of Pokdarwis empowerment depends on transitioning toward a clear collaborative framework, integrated funding through village budgets (APBDes), and facilitative leadership. Synchronized cooperation between the government, private sector (CSR), and the community is essential to transform local assets into a competitive and accountable engine for regional economic growth.